Человек из зеркала: [роман] / Владимир Колычев - Колычев Владимир Григорьевич (Романы о бандитской любви, 2018)
16+ Экземпляры: аб. ЦБ (20190910) / Инвентарный номер: 7169 / Цена: / Авт.знак: К 61 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6